Diversity, abundance and morphological variations of the Xanthopimpla (Ichneumonidae: Pimplinae) in different forest habitats - Ng, Y.F.; Idris, A.B. (Universiti Kebangsaan Malaysia, 2015)
The diversity and abundance of Xanthopimpla (Ichneumonidae: Pimplinae) in the secondary and primary forest of Pasoh Forest Reserve (PFR) were studied. A total of 44 individuals of Xanthopimpla and 16 species were recorded. Fifteen species were recorded from the primary forest and only seven species were recorded from the secondary forest. The X. disjunta, X. guptai maculibasis and X. verrucula verrucula were new records for Malaysia. Meanwhile, X. pleurosticta was new record for Peninsular Malaysia. Shannon Diversity Index (H’) indicated that the Xanthopimpla diversity at the primary forest was significantly higher (p<0.001) than the secondary forest in PFR. This suggests that logging activity would cause depletion on insect diversity. In the secondary forest a total of 20 Xanthopimpla individuals were caught, whereas 24 individuals were caught from the primary forest. The individual of Xanthopimpla abundance in primary forest was not significantly (p>0.05) higher than secondary forest. The species domination in the secondary forest was more pronounced compared to the primary forest. In the secondary forests, X. elegans elegans (30.0%) was the highest percentage of total species representation which was higher compared with X. melanacantha melanacantha (16.7%) and X. honorata honorata (16.7%) in the primary forest. This suggests that logging activity would cause disappearance of certain species of Xanthopimpla and at the same time might have provided an opportunity for some species to be dominant over the other species. The evolution of the Xanthopimpla in term of morphological characters changes were also discussed in this paper.